A Study and Review on Personality and Academic Stress and Their Consequences Among Bachelor and Master Degree Students in North Gujarat - Urvashi Prajapati (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Among students pursuing bachelor's and master's degrees in a variety of academic fields, academic stress has become a major psychological problem. This study looks at the connection between personality traits and academic stress and analyses how it affects students' social environments, mental health, and academic achievement, especially in the North Gujarat region. Students experience academic stress when they believe that the demands of their studies surpass their capacity for coping, frequently as a result of workload, competition, and career uncertainty. Stress perception and management are influenced by personality qualities such as neuroticism, extraversion, and conscientiousness. According to the study, high levels of stress cause anxiety, depression, poor academic performance, and damaged social interactions. Along with discussing stress patterns in a variety of fields, including engineering, law, medicine, and economics, the study offers detection techniques and solutions for stress management. College students are now under additional pressure and stress due to changes in our culture. Due to these students are under a lot of strain and exhibit more symptoms of stress. Stress is the reaction to circumstances or occurrences that interfere with our ability to perform physically or mentally. Sadness, loss of interest or enjoyment, feelings of guilt or low self-worth, trouble sleeping or eating, fatigue, and difficulty concentrating are all signs of depressive disorders.